Prophylactic and Therapeutic Effect of Kynurenine for Experimental Autoimmune Encephalomyelitis (EAE) Disease. (August 2022) - Sundaram, Gayathri; Bessede, Alban; Gilot, David; Staats Pires, Ananda; Sherman, Larry S; Brew, Bruce J; Guillemin, Gilles J
Background: The essential amino acid, tryptophan, is predominantly metabolised through the kynurenine pathway (KP) to generate kynurenine, an aryl-hydrocarbon receptor (AhR) pro-ligand that exerts its effects in a ligand-dependent manner. Interaction between kynurenine and the AhR is an effector mechanism of immunosuppression. We previously found that the KP is involved in multiple sclerosis (MS) disease progression. We postulated that AhR activation by kynurenine might be neuroprotective by encouraging differentiation of Tregs. In this study, we assess both the prophylactic and therapeutic efficiency of kynurenine on disease severity and progression in mice with experimental autoimmune encephalomyelitis (EAE), an MS model. Methods: Myelin oligodendrocyte glycoprotein induced EAE mice (n = 6 per group) were treated with 200 mg/kg L-kynurenine once daily for 10 days beginning on either day 1 of EAE induction (prophylactic) or once they demonstrated motor weakness (therapeutic). Clinical disease severity measured by disease score, time on rotarod, and body weight. Results: The prophylactic kynurenine treatment significantly ( P < .0001) prevented the development of a more severe disease course with mice demonstrating diminished relapse rate and improved clinical and behavioural outcomes. However, therapeutic kynurenine did not significantly ( P = .4463) decrease the clinical signs until 36 days following induction of disease; after 36 days, it also significantly ( P = .0479) reduced disease relapse. Mean body weight measurements only correlated with time on rotarod ( r = −.6410; P = .0007) but not clinical scores ( r = .1925; P = .3674). Conclusions: Kynurenine ameliorates EAE disease progression prophylactically and reduces relapses therapeutically. Further investigations are needed to elucidate the molecular mechanism explaining the therapeutic role of kynurenine for MS.